Análisis de la Causa No. 02331 -2022- 01222, sobre la acción de acceso a la información pública desarrollada en la Unidad Judicial Civil con sede en el cantón Guaranda, referente a la valoración de los medios de prueba y aplicación de la garantía de motivación en el fallo. - Quille Cuvi Luis Nasael (2025)
The case analysis in constitutional matters was carried out on Case No. 02331-2022-01222, which specifically deals with an action of access to public information, the case study has a focus on the assessment of the means of evidence. and application of the guarantee of motivation in the ruling issued by the judge of the Civil Judicial Unit of the Guaranda Canton, which accepts the demand for action for access to public information, which is inadmissible, due to the fact that the public entity acted as is the Ministry of the Environment of the Guaranda Canton, through its Technical Office of the Environment, Water and Ecological Transition, provided at all times the information related to the Drinking Water Board of the Villa Mora Campus requested by Mr. Dionel Manobanda Zurita. In the case, it is identified that the judge did not carry out a correct assessment of the documentary evidence that shows that the public entity does not violate the right to access public information, and it is also identified that the judge in the sentence issued does not comply with the motivation. required in accordance with the facts raised, since it does not disclose how the public entity violates access to public information. It was necessary to complement the case study the use of investigative methodology, which includes the inductive, analytical, and legal method, while the historical, bibliographic, and doctrinal method was used as the type of research, through which information was obtained from the practical legal context that allowed the case study to be supported. KEYWORDS: PRISON CRISIS, PUBLIC POLICIES, REHABILITATION, SOCIAL REINTEGRATION, JOB.